A 104-bp Structural Variation of the ADPRHL1 Gene Is Associated With Growth Traits in Chickens - Li, Tong; Chen, Bingjie; Wei, Chengjie; Hou, Dan; Qin, Panpan; Jing, Zhenzhu; Ma, Haoran; Niu, Xinran; Wang, Chunxiu; Han, Ruili; Li, Hong; Liu, Xiaojun; et al. (Frontiers in Genetics, 2021)
Analyzing marker-assisted breeding is an important method utilized in modern molecular breeding. Recent studies have determined that a large number of molecular markers appear to explain the impact of "lost heritability" on human height. Therefore, it is necessary to locate molecular marker sites in poultry and investigate the possible molecular mechanisms governing their effects. In this study, we found a 104-bp insertion/deletion polymorphism in the 5'UTR of the ADPRHL1 gene through resequencing. In cross-designed F2 resource groups, the indel was significantly associated with weight at 0, 2, 4, 6, and 10 weeks and a number of other traits (carcass weight(CW), semi-evisceration weight (SEW), evisceration weight (EW), claw weight (CLW), wings weight (DWW), gizzard weight (GW), pancreas weight (PW), chest muscle weight (CMW), leg weight (LW), leg muscle weight (LMW), shedding Weight (SW), liver rate(LR), and leg muscle rate (LMR) ) (P < 0.05). In brief, the insertion-insertion (II) genotype was significantly associated with the greatest growth traits and meat quality traits, whereas the values associated with the insertion-deletion (ID) genotype were the lowest in the F2 reciprocal cross chickens. The mutation sites were genotyped in 4628 individuals from 12 different chicken breeds and cross-designed F2 resource groups. The II genotype is the most important genotype in commercial broilers, and the I allele frequency observed in these breeds is relatively high. Deletion mutations tend to be fixed in commercial broilers. However, there is still considerable great potential for breeding in dual-purpose chickens and commercial laying hens. A luciferase reporter assay showed that the II genotype of the ADPRHL1 gene possessed 2.49-fold higher promoter activity than the DD genotype (P < 0.05). We hypothesized that this indel might affect the transcriptional activity of ADPRHL1, thereby affecting the growth traits of chickens. These findings may help to elucidate the function of the ADPRHL1 gene and facilitate enhanced reproduction in the chicken industry.